Stability analysis under diverse environments of fenugreek (Trigonella foenum-graecum) genotypes by AMMI model - YADAV, PREETI; TEHLAN, S K; N, MANOJ KUMAR (The Indian Journal of Agricultural Sciences, 2020)
Fenugreek (Trigonella foenum-graecum L.) is one of the most important seed spices crop in the world. India being one of the largest fenugreek producing country, has released many varieties, but within few years of release, many of these are no longer under cultivation owing to inconsistent performance in diverse environments, however, some of the varieties which depicted stable performance are under cultivation. This study aimed to evaluate the adaptability and yield stability of different fenugreek genotypes using AMMI model. Total 60 elite fenugreek genotypes were evaluated under six environments during rabi 2015–16 and 2016–17 seasons at Vegetable Research Farm, CCS HAU, Hisar. AMMI model was employed to assess the magnitude of genotype × environment (GE) interaction and stability of genotypes across environments. Analysis of variance for seed yield clearly indicates that the mean sum of square for genotypes is significant, suggesting broad range of diversity among the genotypes. The environmental variances are highly significant for most of the characters. G × E mean sum of square was significant for seed yield (q/ha) which indicates that the performance of genotypes that was differential over the environments. The proportion of sum of square for G × E interaction for seed yield was 80.94%. The genotype, viz. JFg 240, HM 346, HM 258, NDM 20, NDM 13 and RM 28 exhibited stable performance over all environments for seed yield. The environments E4 (4 Nov 2016), E3 (28 Nov, 2015) and E2 (15 Nov, 2015) were the main contributors to the phenotypic stability of the genotypes and E2 and E5 are the favourable environments for obtaining higher seed yield.